Winter is coming: What happened in western European mountains between 12.9 and 12.6 ka cal. BP (beginning of the GS1). (26th January 2018) - Tomasso, Antonin; Fat Cheung, Célia; Fornage-Bontemps, Sophie; Langlais, Mathieu; Naudinot, Nicolas
Abstract: This paper builds on recent research on the abrupt cooling event known as GS1 (Younger Dryas) from ca. 12.9 to 11.7 ka cal. BP. These studies have indicated the diversity of local responses to this period between different regions across Europe. Research has indicated both responses and lack of responses of humans to this event in different regions. In accordance with this research, this paper argues that it is necessary to move away from global models of human responses to the analysis of regional scales. We argue that it is necessary to consider the evolutionary dynamics that predated the GS1 cooling event before identifying its potential impact. This paper focuses on this aspect of the problem by considering evidence from three mountainous areas: the Pyrenees, the northern French Alps and Jura, and lastly southern and Apuan Alps. Recently studied sites are considered with specific attention to lithic industries. Our analysis focuses on (1) the identifiable changes in each industry and (2) the relationship with pre-existing cultural and technological dynamics. The analysis has produced two main results. First, there was a tendency towards a decrease in the standardization of blanks, especially in blades, which was common to the different areas. This change, however, predated GS1 and can therefore not be associated with cooling at the start of GS1. Second, the Northern Alps and Jura, in contrast to the two other areas, seems to reveal a break from the lithic technological traditions that occurred around 12.9 ka cal BP or the early stages of GS1. These results enable a discussion of the different mechanisms that can explain differential regional responses to GS1.